Journal of biopesticides (Crop Protection Research Centre, 2008)
The Journal brings together scientists and researchers in the field of ecofriendly crop protection encompassing pests, diseases, weeds, rodents and molluscan pests management thus paving the way for exchange of information and interaction between industry, researchers, academia, students, extension workers and the farmers.